STRATEGI POLITIK PEMENANGAN PARTAI GOLONGAN KARYA (Studi Kasus Tentang Pemilihan Kepala Daerah Kabupaten Bandung) - Surgawan, Ilham; Rudiansah, Bambang; Siam, Nurbaiti Usman (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
The background to this research is that the political strategy carried out by the Golkar party in winning the Bandung Regency regional head election was not yet optimal. Based on these problems, the researcher formulated a problemidentification, namely How the Golongan Karya Party's Political Strategy Wins(Case Study of the Regional Head Election of Bandung Regency). The purposeof this research is to find out and analyze how the political strategy for winning the Golongan Karya Party (Case Study of the Regional Head Election of BandungRegency) by analyzing this research problem, Firmanzah's political marketing theory (Firmanzah 2008:109) is used, which consists of 3 dimensions that influence political strategy. including: Segmentation, Taging and Positioning. Based on this theory, the proposition proposed is